Electronic component
Patent Information
- Application Number
- CN202610478058.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-15
- Filing Date
- 2026-04-13
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]发明要解决的技术问题
Smart Images

Figure CN122968121A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to electronic components. Background Technology
[0002] Patent Document 1 describes a radial lead electronic component. The radial lead electronic component described in Patent Document 1 has a specific structure, which results in excellent vibration resistance and stable holding of the electronic component.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2011-96899 Summary of the Invention
[0006] The technical problem that the invention aims to solve
[0007] The purpose of the exemplary embodiments of the present invention is to provide an electronic component that is not prone to electrostrictive breakdown in a ring wave test.
[0008] Technical means for solving technical problems
[0009] To achieve the above objectives, the electronic component of the present invention, wherein...
[0010] An electronic component comprising: a dielectric substrate; a multilayer electrode film connected to the surface of the dielectric substrate; and a lead portion connected to the surface of the multilayer electrode film.
[0011] The multilayer electrode film has: an innermost electrode layer in contact with the dielectric substrate; and an outermost electrode layer in contact with the lead portion.
[0012] The innermost electrode layer is a Ti film mainly containing Ti, and the outermost electrode layer is a metal film.
[0013] Alternatively, the outermost electrode layer may be a Cu film that mainly contains Cu.
[0014] Alternatively, the thickness of the innermost electrode layer can be 50 nm or more.
[0015] Alternatively, the thickness of the innermost electrode layer can be less than 150 nm.
[0016] Alternatively, the dielectric substrate may contain perovskite oxide as the main component.
[0017] The perovskite oxide may contain one or more elements selected from Ba and Ca as A-site elements, or one or more elements selected from Ti and Zr as B-site elements.
[0018] Alternatively, the proportion of Zr in the perovskite oxide relative to the total amount of Ti and Zr contained as B-site elements may be greater than 0 and less than 0.20 on an atomic basis.
[0019] Alternatively, the dielectric substrate may contain MnO as a secondary component.
[0020] Alternatively, the thickness of the outermost electrode layer can be 50 nm or more and 150 nm or less.
[0021] Alternatively, the multilayer electrode film may include at least one intermediate electrode layer between the innermost electrode layer and the outermost electrode layer.
[0022] Alternatively, the intermediate electrode layer that is in contact with the outermost electrode layer can be used as the outer intermediate electrode layer, which is a Ni film mainly containing Ni.
[0023] Alternatively, the thickness of the outer intermediate electrode layer may be greater than 50 nm and less than 150 nm.
[0024] An inner intermediate electrode layer may be included between the innermost electrode layer and the outer intermediate electrode layer, and the inner intermediate electrode layer may be a Cu film mainly containing Cu.
[0025] Alternatively, the thickness of the inner intermediate electrode layer can be greater than 130 nm and less than 390 nm.
[0026] Alternatively, the thickness of the innermost electrode layer can be set as t1, and the thickness of the inner middle electrode layer can be set as t2, where t2 / t1 is 1.6 or more.
[0027] Alternatively, the multilayer electrode film may be a sputtered film. Attached Figure Description
[0028] Figure 1 This is a schematic diagram of a capacitor.
[0029] Figure 2 It is a schematic diagram of the cross-section of the dielectric substrate and the multilayer electrode film.
[0030] Explanation of reference numerals in the attached figures
[0031] 1…capacitor
[0032] 11…Dielectric element
[0033] 13…Multilayer electrode film
[0034] 13a…Innermost electrode layer
[0035] 13b…Inner intermediate electrode layer
[0036] 13c…outer intermediate electrode layer
[0037] 13d…outermost electrode layer
[0038] 15… Solder
[0039] 17…lead section
[0040] 19…Exterior Design Department Detailed Implementation
[0041] Hereinafter, embodiments of the present disclosure will be described with reference to the accompanying drawings. The embodiments described below are illustrative examples of the present disclosure, and the constituent elements of the embodiments, such as numerical values, shapes, materials, and manufacturing processes, may be changed or modified without causing technical problems. Furthermore, the shapes, etc., shown in the accompanying drawings of this disclosure may not necessarily correspond to actual shapes and dimensions. This is because, in the various drawings, shapes and dimensions have sometimes been changed for illustrative purposes.
[0042] Figure 1 This is a schematic diagram of capacitor 1, which is one of the electronic components disclosed herein. Capacitor 1 is a circular plate capacitor. Circular plate capacitors are mainly used in medium to high voltage applications.
[0043] The capacitor 1 includes: a dielectric substrate 11; a multilayer electrode film 13 formed on two main surfaces of the dielectric substrate 11; a lead portion 17 electrically connected to the multilayer electrode film 13 via solder 15; and an outer casing portion 19 covering the constituent components of the capacitor 1. Furthermore, in Figure 1 In order to show the internal structure of capacitor 1, part of the external assembly 19 has been omitted.
[0044] There are no particular limitations on the composition of the dielectric substrate 11. It may contain perovskite oxide as the main component. There are no particular limitations on the proportion of perovskite oxide in the dielectric substrate 11. When perovskite oxide is used as the main component, it is easy to achieve higher reduction resistance. Although electrostriction is easily increased, the breakdown voltage of the ring wave test described later can be easily improved by using a multilayer electrode film 13 with the innermost electrode layer 13a being a Ti film.
[0045] Perovskite oxides are oxides represented by the formula ABO3, but the ratio of A-site, B-site, and O in perovskite compounds may not conform to the stoichiometric ratio. That is, the ratio of A-site, B-site, and O in perovskite oxides may not be consistent with 1:1:3. The ratio of A-site, B-site, and O in perovskite oxides may deviate from the stoichiometric ratio to the extent that it does not impair the purpose of this disclosure.
[0046] Perovskite oxides can contain one or more elements selected from Ba and Ca as A-site elements, and one or more elements selected from Ti and Zr as B-site elements. Sometimes, a perovskite oxide containing one or more elements selected from Ba and Ca as A-site elements and one or more elements selected from Ti and Zr as B-site elements is called BCTZ.
[0047] In perovskite oxides, the proportion of Ba relative to the total amount of Ba and Ca contained as A-site elements can be greater than 0.7 and less than 1.0 on an atomic basis.
[0048] In perovskite oxides, the proportion of Zr relative to the total amount of Ti and Zr contained as B-site elements can be greater than 0 and less than 0.20 on an atomic number basis. It can be greater than 0.01 and less than 0.20, or greater than 0.08 and less than 0.11. By keeping the Zr content within the above range, the reduction resistance of the dielectric substrate 11 is easily improved. The breakdown voltage of the ring wave test described later is easily improved. Furthermore, the E characteristic is easily ensured.
[0049] The dielectric substrate 11 may also contain MnO as a secondary component. By including MnO as a secondary component in the dielectric substrate 11, the reduction resistance of the dielectric substrate 11 is easily ensured. There is no particular limitation on the content ratio of MnO in the dielectric substrate 11. For example, if the content of the perovskite oxide as the main component is set to 100 parts by weight, it can be more than 0.01 parts by weight and less than 0.08 parts by weight, or more than 0.02 parts by weight and less than 0.04 parts by weight. If the content ratio of MnO is too small or too large, the breakdown voltage in the ring wave test described later will easily decrease.
[0050] The dielectric substrate 11 may also contain components other than perovskite oxide and MnO. Rare earth elements, V, Al, Ni, etc., may also be included without prejudice to the purpose of this disclosure. There are no particular limitations on the proportion of components other than perovskite oxide and MnO.
[0051] There is no particular limitation on the total thickness of the multilayer electrode film 13. For example, it can be greater than 60 nm and less than 1300 nm.
[0052] Figure 2 This is a schematic diagram of a cross-section obtained by cutting the dielectric substrate 11 and the multilayer electrode film 13 along the thickness direction of the multilayer electrode film 13. (See diagram below.) Figure 2 As shown, the multilayer electrode film 13 has at least: an innermost electrode layer 13a in contact with the dielectric substrate 11, and an outermost electrode layer 13d located on the outermost side.
[0053] Furthermore, the multilayer electrode film 13 may also include at least one intermediate electrode layer between the innermost electrode layer 13a and the outermost electrode layer 13d. For example, as Figure 2 As shown, it may also include an outer intermediate electrode layer 13c that contacts the outermost electrode layer 13d. Furthermore, an inner intermediate electrode layer 13b may be included between the innermost electrode layer 13a and the outer intermediate electrode layer 13c.
[0054] The innermost electrode layer 13a is a Ti film mainly containing Ti. That is, the proportion of Ti in the innermost electrode layer 13a is more than 60% on an atomic basis.
[0055] The capacitor disclosed herein, by using a Ti film for the innermost electrode layer 13a, can improve the breakdown voltage in the ring wave test described later. Furthermore, it can improve the adhesion to the dielectric substrate 11. However, when a single-layer Ti film is used instead of the multilayer electrode film 13, the environmental resistance is significantly reduced because Ti is easily oxidized, and the dielectric loss tanδ increases over time. Simultaneously, the dielectric substrate 11 is easily reduced, and the characteristics of the capacitor 1 are easily degraded.
[0056] The thickness of the innermost electrode layer 13a is not particularly limited. For example, it can be 30 nm or more, or 50 nm or more. Alternatively, it can be less than 200 nm, or less than 150 nm. It can be 30 nm or more and less than 200 nm, or 50 nm or more and less than 150 nm. However, if the innermost electrode layer 13a is too thin, the breakdown voltage in the ring wave test is more likely to decrease. Furthermore, the thinner the innermost electrode layer 13a, the more likely its thermal shock resistance is to decrease. Consequently, it is more likely to break down with a relatively low AC voltage, and the deviation of the AC breakdown electric field strength VB is more likely to increase. Conversely, the thicker the innermost electrode layer 13a, the more likely the tanδ of capacitor 1 is to increase. Consequently, it is more likely to break down with a relatively low AC voltage, and the deviation of VB is more likely to increase.
[0057] There are no particular restrictions on the composition of the outermost electrode layer 13d, but the outermost electrode layer 13d can also be a Cu film mainly containing Cu. That is, the proportion of Cu in the outermost electrode layer 13d can be more than 80% on an atomic basis.
[0058] There is no particular limitation on the thickness of the outermost electrode layer 13d. For example, it can be 30nm or more but less than 300nm, or 50nm or more but less than 150nm. If the outermost electrode layer 13d is too thin, the surface of the multilayer electrode film 13 is prone to oxidation and discoloration. Consequently, the solder adhesion of the multilayer electrode film 13 is easily reduced. If the outermost electrode layer 13d is too thick, compared with the case where the outermost electrode layer 13d has an appropriate thickness, various properties are hardly improved while material costs increase.
[0059] The composition of the outer intermediate electrode layer 13c is not particularly limited, but it can also be a Ni film mainly containing Ni. That is, the Ni content in the outer intermediate electrode layer 13c can be 80% or more on an atomic basis. In this case, the outer intermediate electrode layer 13c functions as a solder barrier film.
[0060] There are no particular limitations on the thickness of the outer intermediate electrode layer 13c. For example, it can be 30nm or more but less than 300nm, or 50nm or more but less than 150nm. If the outer intermediate electrode layer 13c is too thin, its high-temperature resistance is prone to decrease. This is because solder erosion is more likely to occur. If the outer intermediate electrode layer 13c is too thick, its thermal shock resistance is prone to deterioration. This is because increased stress can easily lead to film peeling.
[0061] There are no particular restrictions on the composition of the inner intermediate electrode layer 13b, but the inner intermediate electrode layer 13b can also be a Cu film mainly containing Cu. That is, the proportion of Cu in the inner intermediate electrode layer 13b can be more than 80% on an atomic basis.
[0062] There is no particular limitation on the thickness of the inner intermediate electrode layer 13b. For example, it can be 100 nm or more and 500 nm or less, or 130 nm or more and 390 nm or less. If the inner intermediate electrode layer 13b is too thin, the t2 / t1 ratio (described later) tends to decrease if the innermost electrode layer 13a is not thinned. If the innermost electrode layer 13a is thinned, as mentioned above, the breakdown voltage in the ring wave test tends to decrease, the thermal shock resistance tends to decrease, and the deviation of VB tends to increase. If the inner intermediate electrode layer 13b is too thick, the various properties are not improved while the material cost increases compared to the case where the inner intermediate electrode layer 13b has an appropriate thickness. In addition, the thermal shock resistance tends to deteriorate.
[0063] Alternatively, the thickness of the innermost electrode layer 13a can be set as t1, and the thickness of the inner intermediate electrode layer 13b can be set as t2, with t2 / t1 being 1.6 or higher. This makes it particularly effective at reducing the conductivity of the multilayer electrode film 13 at high temperatures. Furthermore, it reduces the likelihood of reduction of the dielectric substrate 11 at high temperatures. If t2 / t1 decreases, the high-temperature resistance is more likely to deteriorate. This is because if t2 / t1 decreases, the conductivity of the multilayer electrode film 13 is more likely to decrease, and the dielectric substrate 11 is more likely to be reduced.
[0064] The following is an explanation of the ring wave test.
[0065] A ring wave is a type of lightning surge. Lightning strikes sometimes occur when using electronic equipment with capacitor 1. The ground potential changes due to the lightning strike. Because of these ground potential changes, high-energy noise is sometimes induced in power distribution lines and communication lines, and sometimes capacitor 1 is electrostrictively broken down due to the noise.
[0066] In the ring wave test, the aforementioned high-energy noise existing in nature is simulated. That is, a high-energy voltage is instantaneously applied to capacitor 1. The maximum value of this voltage is set as the open-circuit voltage. While increasing the open-circuit voltage, the voltage is applied repeatedly, and the magnitude of the open-circuit voltage at which electrostrictive breakdown occurs in dielectric element 11 is taken as the breakdown voltage in the ring wave test.
[0067] If electrostrictive breakdown occurs in the dielectric substrate, multiple cross-sections and longitudinal cracks will appear, as well as breakdown marks and growth ring cracks. That is, electrostrictive breakdown can be confirmed by the appearance of the dielectric substrate 11 after voltage is applied. Furthermore, electrostrictive breakdown can also be confirmed by the sound heard when voltage is applied.
[0068] The higher the dielectric constant of the dielectric element 11, the greater the electrostatic capacitance of the capacitor 1. However, the higher the dielectric constant of the dielectric element 11, the easier it is for electrostriction to increase, and the easier it is for the breakdown voltage in the ring wave test to decrease. In particular, the capacitor 1 of this disclosure increases the breakdown voltage in the ring wave test by making the innermost electrode layer 13a of the multilayer electrode film 13 a Ti film mainly containing Ti, compared with the case of using conventional sintered electrodes.
[0069] The manufacturing method of capacitor 1 will be described below, but there are no particular limitations on the manufacturing method of capacitor 1.
[0070] First, prepare the dielectric substrate 11. There are no particular limitations on the method for preparing the dielectric substrate 11. For example, as the main component of the dielectric substrate 11, prepare powders of oxides of elements such as Ba, Ca, Ti, and Zr, and / or powders of compounds that become oxides through heating. Furthermore, as a secondary component of the dielectric substrate 11, prepare powders of oxides of elements such as Mn, and / or powders of compounds that become oxides through heating.
[0071] Each powder prepared in a manner that yields the main component of the target composition is weighed. Next, the raw material powders of the main component are mixed and pre-fired to obtain a pre-fired powder. Then, the pre-fired powder is mixed with the raw material powders of the secondary components to obtain a mixed powder. Next, the obtained mixed powder is pressed to obtain a molded body. Then, the obtained molded body is sintered to obtain a sintered body. The shape of the obtained sintered body can be appropriately processed. In this way, a dielectric element 11 having a specified composition and shape can be obtained.
[0072] There are no particular restrictions on the mixing method of the powders. For example, all the raw material powders can be mixed at once. In this case, pre-firing can be omitted. Alternatively, a portion of the main component raw material powder can be added to the pre-firing powder along with the secondary component raw material powder without pre-firing.
[0073] Next, a multilayer electrode film 13 is formed on both main surfaces of the dielectric substrate 11. There are no particular limitations on the method for forming the multilayer electrode film 13. For example, it can be formed by sputtering while appropriately modifying the sputtering target. That is, the multilayer electrode film 13 can also be a sputtered film. Alternatively, other thin film formation methods such as ion plating can be used instead of sputtering to form the multilayer electrode film 13.
[0074] Next, the multilayer electrode film 13 is connected to the lead portion 17 via solder 15. Then, the outer casing 19 is formed. There are no particular limitations on the method of forming the outer casing 19. For example, methods such as forming it using resin molding can be cited.
[0075] The electronic components disclosed herein have no particular limitations on their application. They are particularly suitable for applications requiring increased electrostatic capacitance and high breakdown voltage in ring wave tests, i.e., strong surge withstand capability.
[0076] [Example]
[0077] The present disclosure will now be described with reference to more detailed embodiments, but the present disclosure is not limited to these embodiments.
[0078] (Experimental Example 1)
[0079] (Dielectric element)
[0080] BaCO3 powder, CaCO3 powder, TiO2 powder, and ZrO2 powder were prepared as the main raw material powders. MnCO3 powder was prepared as a secondary raw material powder. Each powder was then weighed, and the Ca content ratio (Ca / (Ba+Ca)) relative to the total amount of Ba and Ca contained in the A-site elements, which are the main components contained in the final dielectric substrate, was set to 0.11 on an atomic basis. The Zr content ratio (Zr / (Ti+Zr)) relative to the total amount of Ti and Zr contained in the B-site elements, which are the main components contained in the final dielectric substrate, was set to the values shown in Table 1 on an atomic basis. Furthermore, the total content of A-site elements relative to the total content of B-site elements was set as A / B on an atomic basis, and A / B was set to 1.00.
[0081] The proportion of Mn content relative to 100 parts by weight of the main component contained in the final dielectric matrix is converted to the values shown in Table 1.
[0082] Weighed BaCO3 powder, CaCO3 powder, TiO2 powder, and ZrO2 powder were wet-mixed in a ball mill with water as the solvent for 20 hours. The resulting mixed powder was then pre-calcined at 1100-1220°C for 2 hours to obtain a pre-calcined product containing the main components. Next, while wet-milling the pre-calcined product in a ball mill, MnCO3 powder was added to obtain a mixed powder. An organic binder (polyvinyl alcohol) was added to 100 parts by weight of the obtained mixed powder, and granulation was performed to obtain granular powder.
[0083] The granular powder is pressurized at 100 MPa to obtain a molded body. The molded body is a circular plate with a diameter of 12.5 mm and a thickness of 1.3 mm.
[0084] The resulting molded body was fired in air at a temperature of 1320°C for 2 hours to obtain a sintered body. The sintered body was a circular plate with a diameter of 10.5 mm and a thickness of 1.1 mm.
[0085] In Experimental Example 1, the same composition and shape of dielectric elements were used in all embodiments and comparative examples.
[0086] (Multilayer electrode film)
[0087] In all samples other than Sample No. 1, multilayer electrode films 13 were formed on the two main surfaces of the dielectric substrate. Sputtering was performed while appropriately changing the sputtering target, with the main component metal of each electrode layer being the type shown in Table 1 and the thickness of each electrode layer being the thickness shown in Table 1.
[0088] (Electrode firing)
[0089] In sample No. 1, sintered electrodes made of Cu were formed on the two main surfaces of the dielectric substrate. After heating, a Cu paste containing glass frit was applied to the two main surfaces of the dielectric substrate so that the thickness of the sintered electrodes was 5000 nm (5 μm).
[0090] (Solder adhesion)
[0091] The multilayer electrode film (outermost electrode layer) and the lead terminals (lead section) are connected by solder. Then, the outer casing is made by coating the dielectric substrate with epoxy resin.
[0092] Regarding capacitance C, relative permittivity ε, and tanδ, measurements were performed on the capacitors of each sample at a temperature of 20°C with an AC current of 1 kHz and 1 Vrms applied. A value of ε above 1000 was considered good, and a value of ε above 5000 was considered even better. In Experimental Example 1, C was 4700 pF and ε was 9000 in all examples and comparative examples. tanδ varied depending on the structure of the multilayer electrode film. The measurement results of tanδ are shown in Table 1. A value of tanδ below 2.5% was considered good, and a value of tanδ below 1.4% was considered even better.
[0093] Regarding the insulation resistance IR, a 500V DC current was applied across the capacitor of each sample, and measurements were taken at a temperature of 20°C. In Experimental Example 1, the IR of all samples was 3.0 × 10⁻⁶. 5 MΩ.
[0094] Regarding the AC breakdown electric field strength VB, an AC electric field was gradually increased across the capacitors of each sample. The electric field value at the moment a 100mA leakage current flows is defined as VB. For each sample, VB was measured for 10 capacitors, and the average value (Av.) and standard deviation (σ) of VB are shown in Table 1. The results are presented in Table 1. A VB average value above 8.0 kV / mm is considered good. A VB standard deviation below 6.0 kV / mm is considered good, and below 4.0 kV / mm is considered even better.
[0095] In the ring wave test, firstly, a ring wave with an open-circuit voltage of 4.0 kV and a frequency of 100 kHz was applied 20 times to the capacitor of each specimen. Then, the ring wave was applied 20 times under the same conditions, except that the direction of voltage application was reversed. Electrostrictive breakdown at that moment was confirmed by observing the sound during the application of the ring wave and the appearance of each specimen after the application of the ring wave.
[0096] Next, for capacitors that did not experience electrostrictive breakdown, the open-circuit voltage was increased by 1 kV and the same test was performed. The same test was repeated by increasing the open-circuit voltage by 1 kV each time until electrostrictive breakdown occurred. The open-circuit voltage at which electrostrictive breakdown occurred was taken as the breakdown voltage. Furthermore, the breakdown voltage was measured for 10 capacitors of each sample, and the average breakdown voltage of each sample is shown in Table 1.
[0097] Solder adhesion was evaluated using Sn-3.0Ag-0.5Cu lead-free solder (Senju Metal Industries, Ltd.: M705). Before solder adhesion, each capacitor sample was immersed in non-reactive rosin flux. Then, it was immersed in a solder bath at 245±2°C for 3 seconds. The area covered by the new solder was calculated for the capacitor after immersion in the solder bath. A wetted area of 95% or more was defined as good, 90% to less than 95% as acceptable, and less than 90% as unacceptable. The results are shown in Table 1. There were actually no samples with unacceptable solder adhesion.
[0098] For each capacitor sample after solder adhesion, a high-temperature load test was conducted at 125°C, with an applied voltage of 1000Vac, and a test duration of 2000 hours. When comparing the IR of the capacitor before and after the high-temperature load test, a decrease in IR of less than 1 bit was defined as "Good," a decrease of 1 bit or more but less than 2 bits was defined as "Acceptable," and a decrease of more than 2 bits was defined as "Unacceptable." The results are shown in Table 1. In fact, no sample failed the high-temperature load test.
[0099] Regarding the thermal cycling test, one heat treatment cycle consisting of steps (i) to (iv) was performed on the capacitors after solder adhesion. One heat treatment cycle consisted of the following steps: (i) holding the sample at a temperature of -55°C for 30 minutes; (ii) raising the sample temperature to 125°C within 3 minutes; (iii) holding the sample at 125°C for 30 minutes; and (iv) cooling the sample temperature to -55°C within 3 minutes.
[0100] For each sample, the electrostatic capacitance of each capacitor was measured after one heat treatment cycle of 3000 cycles (10 capacitors). The proportion of capacitors whose electrostatic capacitance (C) decreased by more than 20% compared to before the repeated heat treatment cycles was calculated as the failure rate. Cases with a failure rate less than 10% (no failures) were classified as "Good"; cases with a failure rate between 10% and 20% (1-2 failures) were classified as "Acceptable"; and cases with a failure rate exceeding 20% (3 or more failures) were classified as "Unacceptable". The results are shown in Table 1. In reality, no samples were deemed unacceptable after the heat cycling test.
[0101]
[0102] Comparing Sample No. 1 and Sample No. 2, the types and shapes of the electrode layers are different. However, even if, as in Sample No. 2, both the innermost and outermost electrode layers use multilayer electrode films with Cu as the main component, the results of the ring wave test are no different from those of Sample No. 1, which uses sintered electrodes with Cu as the main component.
[0103] Furthermore, regarding sample No.2, the results of the ring wave test remained unchanged regardless of whether the thickness of the innermost electrode layer was varied within the range of 180nm to 600nm, the thickness of the outer middle electrode layer was varied within the range of 30nm to 300nm, or the thickness of the outermost electrode layer was varied within the range of 30nm to 300nm.
[0104] In Experimental Example 1, the improvement rate of the breakdown voltage relative to the breakdown voltage of Specimen No. 1 in the ring wave test was evaluated. Specifically, an improvement rate of 25% or more was defined as good, and an improvement rate of 50% or more was defined as even better. The same results were obtained when the improvement rate of the breakdown voltage relative to the breakdown voltage of Specimen No. 2 in the ring wave test was evaluated.
[0105] Samples No. 3a and 3-6 are samples with a two-layer structure where the innermost electrode layer of sample No. 2, which is mainly composed of Cu, is a Ti-based innermost electrode layer and an inner intermediate electrode layer mainly composed of Cu, and the thickness of the innermost electrode layer is varied. The results of the ring wave test for samples No. 3a and 3-6, where the innermost electrode layer is mainly composed of Ti, are good. Furthermore, the results of all other tests are also good.
[0106] Specimens No. 7 to 18 were tested under the same conditions as Specimens No. 4, except that the thicknesses of the inner intermediate electrode layer, the outer intermediate electrode layer, or the outermost electrode layer were varied. Like Specimens No. 4, Specimens No. 7 to 18 showed good results in the ring wave test. Furthermore, all other test results were also good.
[0107] Specimens No. 19 and 20 were tested under the same conditions as Specimens No. 6, except that the thickness of the inner intermediate electrode layer was varied. Like Specimens No. 6, Specimens No. 19 and 20 showed good results in the ring wave test. Furthermore, all other test results were also good.
[0108] Specimens No. 21-23 were tested under the same conditions as Specimens No. 4, except that the thicknesses of the innermost electrode layer and the inner intermediate electrode layer were varied. Like Specimens No. 4, Specimens No. 21-23 showed good results in the ring wave test. Furthermore, all other test results were also good.
[0109] Samples No. 24 to 28 were prepared under the same conditions as Sample No. 4, except that the MnO content in the dielectric matrix was varied. The MnO content in each sample was trace, therefore, even with variations in the MnO content, the test results other than the ring wave test remained unchanged. Furthermore, it was confirmed that the results of the ring wave test changed according to the change in the MnO content.
[0110] Samples No. 28 and 29 differ from samples No. 3 to 27 in that their innermost electrode layer is composed primarily of Ni. When the innermost electrode layer is composed primarily of Ni, the improvement rate of breakdown voltage in the ring wave test does not increase sufficiently.
[0111] (Experimental Example 2)
[0112] In Experiment 2, unlike in Experiment 1, the composition and shape of the dielectric element were changed.
[0113] The Ca content ratio (Ca / (Ba+Ca)) relative to the total amount of Ba and Ca contained in the A-site elements of the final dielectric substrate (BCTZ) is 0 on an atomic basis. That is, only Ba was used as the A-site element. The Zr content ratio (Zr / (Ti+Zr)) relative to the total amount of Ti and Zr contained in the B-site elements of the final dielectric substrate (BCTZ) is 0. That is, only Ti was used as the B-site element.
[0114] The dielectric element is designed as a circular plate with a diameter of 4.5 mm and a thickness of 1.0 mm. C is 470 pF, ε is 3000, and IR is 1.0 × 10⁻⁶. 6 MΩ.
[0115] Sample No. 31 used a Cu-based sintered electrode, similar to Sample No. 1. However, the thickness of the sintered electrode was changed to 4000 nm (4 μm). Sample No. 32 used an electrode multilayer film with the same structure as the embodiments in Experimental Example 1 for the aforementioned dielectric substrate. The results are shown in Table 2. Furthermore, the improvement rate of the ring wave test was set as the improvement rate relative to the breakdown voltage of Sample No. 31.
[0116]
[0117] In comparison with the samples of Experimental Example 1, the results of the ring wave test for samples No. 31 and 32 changed mainly with the change of the dielectric element. Moreover, the results of the ring wave test for sample No. 32 were improved compared with those of sample No. 31 by using a multilayer electrode film with a specific composition.
[0118] (Experimental Example 3)
[0119] Sample No. 51 was subjected to the same conditions as Sample No. 4, except that it used a multilayer electrode film with a two-layer structure of Ti as the innermost electrode layer and Cu as the outermost electrode layer. Sample No. 52 was subjected to the same conditions as Sample No. 4, except that it used a multilayer electrode film with a two-layer structure of Ti as the innermost electrode layer and Ni as the outermost electrode layer. The results are shown in Table 3.
[0120]
[0121] Table 3 confirms that the results of the ring wave test were significantly improved when at least the innermost electrode layer used a multilayer electrode film with Ti as the main component.
Claims
1. An electronic component, wherein, An electronic component comprising: a dielectric substrate; a multilayer electrode film connected to the surface of the dielectric substrate; and a lead portion connected to the surface of the multilayer electrode film. The multilayer electrode film has: an innermost electrode layer in contact with the dielectric substrate; and an outermost electrode layer in contact with the lead portion. The innermost electrode layer is a Ti film mainly containing Ti, and the outermost electrode layer is a metal film.
2. The electronic component according to claim 1, wherein, The outermost electrode layer is a Cu film that mainly contains Cu.
3. The electronic component according to claim 1 or 2, wherein, The thickness of the innermost electrode layer is 50 nm or more.
4. The electronic component according to claim 1 or 2, wherein, The thickness of the innermost electrode layer is less than 150 nm.
5. The electronic component according to claim 1 or 2, wherein, The dielectric matrix contains perovskite oxide as the main component.
6. The electronic component according to claim 5, wherein, The perovskite oxide contains one or more elements selected from Ba and Ca as A-site elements, and one or more elements selected from Ti and Zr as B-site elements.
7. The electronic component according to claim 6, wherein, In the perovskite oxide, the proportion of Zr contained relative to the total amount of Ti and Zr contained as B-site elements is greater than 0 and less than 0.20 on an atomic basis.
8. The electronic component according to claim 5, wherein, The dielectric matrix contains MnO as a secondary component.
9. The electronic component according to claim 1 or 2, wherein, The thickness of the outermost electrode layer is greater than 50 nm and less than 150 nm.
10. The electronic component according to claim 1 or 2, wherein, The multilayer electrode film includes at least one intermediate electrode layer between the innermost electrode layer and the outermost electrode layer.
11. The electronic component according to claim 10, wherein, The intermediate electrode layer that is in contact with the outermost electrode layer is designated as the outer intermediate electrode layer, which is a Ni film mainly containing Ni.
12. The electronic component according to claim 11, wherein, The thickness of the outer intermediate electrode layer is greater than 50 nm and less than 150 nm.
13. The electronic component according to claim 11, wherein, An inner intermediate electrode layer is included between the innermost electrode layer and the outer intermediate electrode layer, and the inner intermediate electrode layer is a Cu film mainly containing Cu.
14. The electronic component according to claim 13, wherein, The thickness of the inner intermediate electrode layer is greater than 130 nm and less than 390 nm.
15. The electronic component according to claim 13, wherein, The thickness of the innermost electrode layer is set as t1, and the thickness of the inner middle electrode layer is set as t2, where t2 / t1 is 1.6 or more.
16. The electronic component according to claim 1 or 2, wherein, The multilayer electrode film is a sputtered film.
Citation Information
Patent Citations
Radial lead electronic component
JP2011096899A